Expression of adipokines in osteoarthritis osteophytes and their effect on osteoblasts - Junker, Susann; Frommer, Klaus W.; Krumbholz, Grit; Tsiklauri, Lali; Gerstberger, Rüdiger; Rehart, Stefan; Steinmeyer, Jürgen; Rickert, Markus; Wenisch, Sabine; Schett, Georg; Müller-Ladner, Ulf; Neumann, Elena (Matrix Biology, 2016)
Osteophyte formation in osteoarthritis (OA) is mediated by increased osteoblast activity, which is -in turn- regulated by the Wnt signaling pathway. Obesity is regarded a risk factor in OA, yet little is known about the interaction between adipose tissue-derived factors, the adipokines, and bone formation, although adipokines are associated with the pathogenesis of OA. Therefore, the effect of adipokines on bone and cartilage forming cells and osteophyte development was analyzed.Human OA osteophytes were histologically characterized and adipokine expression was evaluated by immunohistochemistry. Osteoblasts and chondrocytes were isolated from OA tissue and stimulated with adiponectin, resistin, or visfatin. Cytokine and osteoblast/chondrocyte markers were quantified and activation of Wnt and p38 MAPK signaling was analyzed.Adiponectin, resistin, and visfatin were expressed in OA osteophytes by various articular cell types. Stimulation of OA osteoblasts with adiponectin and of OA chondrocytes with visfatin led to an increased release of proinflammatory mediators but not to osteoblast differentiation or activation. Additionally, visfatin increased matrix degrading factors in chondrocytes. Wnt signaling was not altered by adipokines, but adiponectin induced p38 MAPK signaling in osteoblasts.Adipokines are present in OA osteophytes, and adiponectin and visfatin increase the release of proinflammatory mediators by osteoblasts and chondrocytes. The effects of adiponectin were mediated by p38 MAPK but not Wnt signaling in osteoblasts. Therefore, the results support the idea that adipokines do not directly influence osteophyte development but the proinflammatory conditions in OA.
EVALuna2:13376